‘Normalizing’ the malignant phenotype of luminal breast cancer cells via alpha(v)beta(3)-integrin - Abu-Tayeh, Hanan; Thaler, Sonja; Sleeman, Jonathan P. (Cell death & disease, 2016)
Reestablishing tissue organization of breast cancer cells into acini was previously shown to override their malignant phenotype. In our study, we demonstrate that alpha(v)beta(3) integrin (Int-αvβ3), previously shown to play a role in cancer progression, promoted differentiation and growth arrest of organoids derived from luminal A breast cancer cells grown in their relevant three-dimensional microenvironment. These organoids differentiated into normal-like acini resembling a benign stage of breast tissue. Likewise, we demonstrate that Int-αvβ3 is selectively expressed in the epithelium of the benign stage of breast tissues, and is lost during the early stages of luminal A breast cancer progression. Notably, the organoids’ reversion into normal-like acini was mediated by cancer luminal progenitor-like cells expressing both EpCAMhighCD49flowCD24+ and Int-αvβ3. Furthermore, downregulation of Notch4 expression and downstream signaling was shown to mediate Int-αvβ3-induced reversion. Intriguingly, when luminal A breast cancer cells expressing Int-αvβ3 were injected into a humanized mouse model, differentiated tumors developed when compared with that generated by control cells. Hence, our data suggest that promoting differentiation of luminal A breast cancer cells by signaling emanating from Int-αvβ3 can potentially promote ‘normalization’ of their malignant phenotype and may prevent the malignant cells from progressing.